PRACTICAL METHOD FOR ASSESSING RESERVOIR PERFORMANCE TO REVIVE CLOSED OIL WELLS - Usman Pasarai (Scientific Contributions Oil and Gas, 2014)
Efficiency is the key issue in reinstating of closed oil wells to production. The goal of this work is to develop practical workÃ€ow for assessing reservoir performance to revive closed wells. The workÃ€ow are generating the set of criteria, valuing the criteria, and making a ranked list of wells to be revived. Application to an offshore oil field, which under consideration to start producing again shown that the results are found to be reliable and consistent with the historical production performance. From the nine wells assessed, found that Well 3 and Well 7 are not recommended to be revived due to low remaining reserves and less predicted additional recoverable oil. The proposed methodology focus on petrophysical and production performance analysis associated with the wells probed rather than integrating static-dynamic reservoir data, well data, and operational issues as the commonly used one.,. Application of this methodology are expected to be beneficial to companies involved in field operations because the cost associated with the time spent for these types of processes could be reduced considerably.